Creative marginalization of gender: a discourse analysis of advertisements in Pakistani newspapers - Musarat Yasmin; Farhat Naseem; Malik Hassan Raza (Creativity Studies, 2018)
Creative industries have been considered crucial to the economic well-being of any country. Besides the economy, the advertising industry has been investigated in West for its influence on the minds of its consumers. Pakistan has a diversity of culture and impact of creative industries on common people is not studied yet. The present study analyses the advertising discourse to explore gender construction through language and visuals in Pakistani print media. The sample includes four national English newspapers collected over a period of one month. An asymmetrical and stereotypical portrayal of women emerges from discourse analysis. Along with gender-specific language, images are constructed to render women marginalised as compared to men in Pakistani society. Results imply that creative industries have a potential to exert an ever-lasting impact on mass-mind but have become a tool in the hands of influential people.